Preliminary survey on knowledge, attitudes and practices regarding rabies - Muthunuwan, J.T.; Ganhewa, A.G.K.H.; Perera, H.D.S.C.; Hishaam, M.; Bandara, W.M.M.S.; Gunasekera, H.A.K.M. (Sri Lankan Society for Microbiology, 2017)
Attached

Introduction: The Ministry of Health's goal is to reduce the number of human deaths from rabies to zero by 2020. Community awareness and responsible behaviour of pet owners are key factors to achieve this goal. Knowledge, attitude and practices (KAP) regarding rabies has been reported only from the Kandy district. We describe a preliminary survey among outpatients in Colombo, to supplement existing knowledge. Methods: A convenience sample (n = 200) was selected from 26th March to 8th April 2016, from outpatients of the National Hospital of Sri Lanka. Data was collected using a selfadministered questionnaire. Results: The majority were females (66.5%), Buddhist (80.5%) and from the Colombo District (58.5%). More than 75% of the subjects knew that dogs were the main reservoir of rabies, transmission was by biting, that washing the wound was important and that rabies could be prevented by vaccinating dogs and humans. However, only 22.5% were aware that rabies was fatal after development of disease. There was a lack of knowledge regarding other animal reservoirs, other modes of transmission and clinical features of rabid animals. Pet owners were more likely to have been bitten by a dog than those who did not own pets (p<0.05). However, only half of the respondents admitted that their pets had been vaccinated during the last year. Conclusion: Future health educational programs should highlight the risks of rabies transmission by animals other than dogs and methods of transmission other than bites as well as the clinical features of rabies for easy identification of rabid animals. The message that vaccination after developing the disease does not change the outcome needs to be clearly presented. Reasons for non compliance of dog vaccination needs to be investigated and rectified.
Keywords: Rabies, Sri Lanka, Knowledge